Comparison of Two Paradigms Based on Stimulation with Images in a Spelling Brain–Computer Interface - Ron-Angevin, Ricardo; Fernández-Rodríguez, Álvaro; Dupont, Clara; Maigrot, Jeanne; Meunier, Juliette; Tavard, Hugo; Lespinet-Najib, Véronique; André, Jean-Marc (IOAP-MDPI, 2023)
A P300-based speller can be used to control a home automation system via brain activity. Evaluation of the visual stimuli used in a P300-based speller is a common topic in the field of brain–computer interfaces (BCIs). The aim of the present work is to compare, using the usability approach, two types of stimuli that have provided high performance in previous studies. Twelve participants controlled a BCI under two conditions, which varied in terms of the type of stimulus employed: a red famous face surrounded by a white rectangle (RFW) and a range of neutral pictures (NPs). The usability approach included variables related to effectiveness (accuracy and information transfer rate), efficiency (stress and fatigue), and satisfaction (pleasantness and System Usability Scale and Affect Grid questionnaires). The results indicated that there were no significant differences in effectiveness, but the system that used NPs was reported as significantly more pleasant. Hence, since satisfaction variables should also be considered in systems that potential users are likely to employ regularly, the use of different NPs may be a more suitable option than the use of a single RFW for the development of a home automation system based on a visual P300-based speller.
Keywords: Automatización; Brain–computer interface (BCI); Event-related potential (ERP); Row-column paradigm (RCP); Stimulus; Face; Picture